Cost of diabetic foot disease to the National Health Service in England. Issue 12 (1st August 2014) - Kerr, M.; Rayman, G.; Jeffcoate, W. J.
Abstract Aim To estimate the annual cost of diabetic foot care in a universal healthcare system. Methods National datasets and economic modelling were used to estimate the cost of diabetic foot disease to the National Health Service in England in 2010–2011. The cost of hospital admissions specific to foot disease or amputation was estimated from Hospital Episode Statistics and national tariffs. Multivariate regression analysis was used to estimate the impact of foot disease on length of stay in admissions that were not specific to foot disease or amputation. Costs in other areas were estimated from published studies and data from individual hospitals. Results The cost of diabetic foot care in 2010–2011 is estimated at £580m, almost 0.6% of National Health Service expenditure in England. We estimate that more than half this sum (£307m) was spent on care for ulceration in primary and community settings. Of hospital admissions with recorded diabetes, 8.8% included ulcer care or amputation. Regression analysis suggests that foot disease was associated with a 2.51‐fold (95% CI 2.43–2.59) increase in length of stay.The cost of inpatient ulcer care is estimated at £219 m, and that of amputation care at £55 m. Conclusions The cost of diabetic foot disease is substantial. Ignorance of the cost of current care may hinder commissioning of effective services for prevention and management in both community and secondary care.